A relação entre a afetividade e a psicomotricidade - Trevelin, Guilherme (My University, 2019)
Introduction: Feelings like affection and refuge are very important to trigger processes into people?s life, by means of this focusing on human movement inside the school environment, this present study will pursue explanations to relate the issues of affectivity with the child's motricity. In such a way, the following study contemplates the research carried out in the discipline of Trabalho de Conclusão de Curso I, in the Physical Education Degree, at the University of Caxias do Sul, carrying the study around physical education classes in the public education system. Objectives: The main aim is to analyze the implications that teachers establish between the relation of psychomotricity and affectivity in physical education classes within children between 3 and 4 years old inside the public-school system. Methods: The method used to this present study was the qualitative method of research. The assortment of data and information was made through 8 observations of a physical education teacher in a kindergarten school. Based on the information obtained by the questionnaires, data analysis was performed for further interpretation and to present results (sic).
Introdução: Os sentimentos de afeto e acolhimento são muito importantes para desencadearem processos em nossa vida, com isso trazendo o foco para a área do movimento humano no âmbito escolar, este presente estudo buscará explicações para relacionar as questões da afetividade com a motricidade infantil. Nesse sentido, o estudo sequente, contempla a pesquisa realizada na disciplina de Trabalho de Conclusão de Curso I, no Curso de Licenciatura em Educação Física, na Universidade de Caxias do Sul sobre as aulas de educação física na educação infantil da rede pública de ensino. Objetivos: O objetivo geral consiste analisar quais as implicações que os professores constituem em relação entre a psicomotricidade e a afetividade nas aulas de educação física com crianças entre 3 e 4 anos de idade da rede pública de ensino. Métodos: A pesquisa é caracterizada pelo método e qualitativo. A coleta de dados e informações será através de 8 observações de um(a) professor(a) de educação física na educação infantil. A partir das informações obtidas pelos questionários, será realizada a análise dos dados para posterior interpretação e apresentação de resultados (sic).
Keywords: Educação física; Educação de crianças; Psicomotricidade